2017
DOI: 10.1136/thoraxjnl-2017-210598
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for oxygen saturation from sea level to the highest human habitation in the Andes in acclimatised persons

Abstract: Oxygen saturation, measured by pulse oximetry (SpO), is a vital clinical measure. Our descriptive, cross-sectional study describes SpO measurements from 6289 healthy subjects from age 1 to 80 years at 15 locations from sea level up to the highest permanent human habitation. Oxygen saturation measurements are illustrated as percentiles. As altitude increased, SpO decreased, especially at altitudes above 2500 m. The increase in altitude had a significant impact on SpO measurements for all age groups. Our data pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 9 publications
1
48
1
1
Order By: Relevance
“…This statistical model is therefore highly dependent on the data included in the modelling process. This is illustrated by the observed mismatch between this model and the empirical data sets obtained by Rojas-Camayo et al [13] as well as our own data collection in the IHIP-2 trial. On the one hand, the statistical model was built using aggregated data collected from mixed populations while using pulse oximeters with partially unknown specifications.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This statistical model is therefore highly dependent on the data included in the modelling process. This is illustrated by the observed mismatch between this model and the empirical data sets obtained by Rojas-Camayo et al [13] as well as our own data collection in the IHIP-2 trial. On the one hand, the statistical model was built using aggregated data collected from mixed populations while using pulse oximeters with partially unknown specifications.…”
Section: Discussionmentioning
confidence: 67%
“…to avoid extrapolation errors. Instead of the LMS method used by Rojas-Camayo et al [13], we reported the centiles of their data with a lowess smoother. To visualise the difference between the various hypoxemia thresholds that have been proposed, we graphically compared the altitude-adaptive abnormal SpO 2 threshold, the statistical hypoxemia threshold, and the WHO definition for oxygen administration (90%) with the 2.5 th centile (lowess smoothed) reported by Rojas-Camayo et al [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations